Survey of Indian history - "Panikkar, K. M" (Bombay, 1954)
This Survey of Indian History was published originally on the 15th August 1947, the date of India's independence. Since then it has been reprinted many times and may, therefore, be said to have achieved the position of a popular favourite, an unusual distinction for a historical work. Born in 1895, Sardar K M Panikkar was educated in Madras and Oxford. He was a scholar of Christ Church and was later called to the Bar (Middle Temple).
Keywords: India-History